Legal Truth (Menakar Kebenaran Hukum) - Prasetyo, Yogi (Universitas Muhammadiyah Ponorogo, 2017)
Law as part of human knowledge have various views on the truth. The legal truth is more likely to be assessed according to the perception and point of view of each one, the truth of the law will be assessed in accordance with the standards of the existing measures on him. Not infrequently respective claims to truth are obtained, causing antagonism and conflict. For that we would need to measure the truth of the law into a theorization. Legal correspondence theory of truth to understand the truth as empirical reality sensory contained in the community, to get this truth by the method of inductive reasoning, which draw conclusions from the events that are specific to the incidence of common law. The coherence theory of truth to understand the law as a result of conceptual ideas of rational logic of human reason, to obtain this truth by the method of deductive reasoning, which draw conclusions from the events that are common to a special legal events. While the pragmatic theory of truth law basing the truth if it can provide benefits for humans.